Puasa Dalail Al-Quran Dalam Keseimbangan Teologis dan Kesehatan - Nasikhin, Baiti Al Ami; Lutfiyah, (Tasamuh: Jurnal Studi Islam, 2025)
This study employs a systematic approach to literature selection, incorporating both primary and secondary sources to ensure validity, relevance, and methodological quality. The research examines the practice of Dalail alQur’an fasting from Islamic legal and health perspectives, utilizing a comprehensive literature review that includes religious texts such as the Qur’an and Hadith, as well as scholarly works and scientific journals published within the last decade. Data validation was conducted through source triangulation to enhance objectivity and reliability, while qualitative descriptive analysis was used to integrate religious and medical viewpoints. The findings indicate that Dalail al-Qur’an fasting is a unique form of voluntary fasting (dahr) combined with the monthly recitation of the entire Qur’an, excluding prohibited fasting days such as Eid. While it offers spiritual enrichment and potential health benefits like detoxification and improved metabolism, critical evaluation is necessary due to possible risks related to nutritional deficiency and mental fatigue, particularly when practiced without proper guidance or individual assessment. This study contributes a balanced, interdisciplinary perspective on the integration of religious practice and health outcomes, emphasizing the importance of responsible implementation in line with both Sharia principles and medical recommendations.